Verba volant, scripta manent - Rizvi, Fazal (Vasl Artists' Collective, 2015)
Artist Residency: Between thinking, seeing & saying nothing- An Anthology of Sorts.
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Pakistan